The Role of Media in Shaping Narrative about the Impact of Drone Strikes on Insurgency in Pakistan - Abdul Basit Khan; Abdul Nafey; Hidayat Ullah, (ASIAN Journal of International Peace & Security (AJIPS), 2023)
This study focuses on the impact of drone strikes on insurgency in Pakistan and the role of media in positive and negative narrative building in the context of drone strikes. It describes how the public perspective about drone strikes is different in the US and Pakistan, and what is the role of media in shaping it. The data was collected through secondary sources such as books, research articles, and online news sources. The data is analyzed through a qualitative method of research under which a thematic approach is used. The objective of this study is to show the actual impact of drone strikes on insurgency in Pakistan. The data shows that the drone strikes reduced the militant attacks, but at the expense of further deteriorating the situation in some cases, and areas. The second objective is to explore the role of media in shaping narrative. The masses in Pakistan deem these attacks as violations of the rules of International Law. While the masses in the United States mostly support drone strikes. Mainly, public opinion is based on the narrative introduced by the media networks they are watching.